Design and Analysis of ECVT on Electric Powered Vehicles for Determining the Speed Ratio - Himmawan Sabda Maulana; I Nyoman Sutantra (JMES: The International Journal of Mechanical Engineering and Sciences, 2021)
Electronics Continuous Variable Transmission (ECVT) is a smart transmission that has unlimited gear ratios. By analyzing vehicle conditions, ECVT can choose the most efficient gear ratio. ECVT mode requires a Planetary Gear Set (PGS) as a power splitter. This research will use PGS and double electric motor to combine the ECVT mode with electric vehicles to determine the desired speed ratio. The PGS was designed by an analytical model and simulated using CAD software. The simulation will provide several input variations to get the right speed ratio, such as speed variations and rotational direction. The analytical model obtained a PGS ratio of 1:6 with 19 sun gear teeth, 95 ring gear teeth, 38 planet gear teeth, and a motor power of 47 kW. Simulation results will be applied to build the prototype that will be made with a 3D printer. This study shows that ECVT can be a transmission system for electric vehicles with 2 to 5 levels of transmission, and using double electric motors with small power can replace an electric motor with large power. To obtain maximum efficiency, a good control strategy is needed. The control strategy will be discussed in further research.